2021
DOI: 10.3389/fimmu.2021.664212
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant BCG Vaccine Is Safe and Immunogenic in Neonatal Calves and Reduces the Clinical Disease Caused by the Respiratory Syncytial Virus

Abstract: The human respiratory syncytial virus (hRSV) constitutes a major health burden, causing millions of hospitalizations in children under five years old worldwide due to acute lower respiratory tract infections. Despite decades of research, licensed vaccines to prevent hRSV are not available. Development of vaccines against hRSV targeting young infants requires ruling out potential vaccine-enhanced disease presentations. To achieve this goal, vaccine testing in proper animal models is essential. A recombinant BCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…Further, this vaccine was shown to be safe and immunogenic in human adult volunteers. In the model of neonatal calves, this type of immunization increased virus-specific IgA and virus-neutralization activity in nasal fluid and increased the proliferation of virus- and BCG-specific CD4+ and CD8+ T cells in lymph nodes supporting the notion that this vaccine approach could be considered as a candidate for infant immunization against RSV [ 201 ]. RSV may induce an inappropriate Th2-type immune response, which causes severe pulmonary inflammation.…”
Section: Immunity To Npmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, this vaccine was shown to be safe and immunogenic in human adult volunteers. In the model of neonatal calves, this type of immunization increased virus-specific IgA and virus-neutralization activity in nasal fluid and increased the proliferation of virus- and BCG-specific CD4+ and CD8+ T cells in lymph nodes supporting the notion that this vaccine approach could be considered as a candidate for infant immunization against RSV [ 201 ]. RSV may induce an inappropriate Th2-type immune response, which causes severe pulmonary inflammation.…”
Section: Immunity To Npmentioning
confidence: 97%
“…Given the extensively accepted safety and immunogenicity profile of the bacillus Calmette–Guérin (BCG) vaccine in newborns, the vaccine based on the recombinant BCG expressing NP of RSV (rBCG-N-hRSV) is intended for direct use on neonates to prevent severe hRSV infection [ 201 ]. A phase I clinical trial rBCG-N-hRSV vaccine showed that the vaccine was safe; serum IgG antibodies directed against M. bovis and the N-protein of RSV increased after vaccination, as well as the cellular response, consisting of IFN-γ and IL-2 production against PPD and the N-protein.…”
Section: Vaccines Based On Npmentioning
confidence: 99%
“…Briefly, randomly selected samples, ~0.5 g each, lesioned and non-lesioned lung tissues were collected from two separate lung lobes each calf and stored in RNAlater (ThermoFisher). RNA was then isolated and pooled from the separate locations (lesioned samples pooled together, non-lesioned lung tissues pooled together) using Trizol Reagent (Life Technologies) and then cleaned up using a Qiagen RNeasy isolation column, as described ( 14 ). Nasal swabs samples were collected from the upper nasal cavity of BRSV infected calves on days 0, 3, 7, 10, and 14 after infection.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-seven, 1- to 2-d-old Holstein × Angus calves (12 males and 15 females) were enrolled in the trial. A statistical power analysis was performed for sample size estimation based upon published results (including our own; Castrucci et al, 1996 , 1998 ; Nickell et al, 2016 ; Guerra-Maupome et al, 2019 ; Mahmoud et al, 2020 ; Wheat et al, 2020 ; Díaz et al, 2021 ) for in vivo innate immunostimulant activity in cattle. Given a medium effect size (following Cohen’s criteria, Cohen, 1988 ), an α = 0.05, and power = 0.7, the projected samples size to measure a significant effect of SCFP supplementation on gross lung pathology scores (in challenge studies, Mann–Whitney test) was n = 12, calculated using the G*Power 3.1 software.…”
Section: Methodsmentioning
confidence: 99%